Novel silver complexes with popular non-steroidal anti-inflammatory drugs - Karolina Kafarska; Wojciech M. Wolf (ACTA INNOVATIONS, 2016)
Non-steroidal anti-inflammatory drugs (NSAID) are class of drugs with antipyretic, analgesic and antiinflammatory properties. They have also exhibited anti-tumor activity. Even though the mode of their antiinflammatory activity action is well understood, they exhibit significant adverse effects. Metal complexesation with NSAID may be a promising option for side effects reduction. The novel silver complexes with commonly used non-steroidal anti-inflammatory drugs: ibuprofen, naproxen, mefenamic acid and ketoprofen, were synthesized and characterized by elemental analysis, IR- spectroscopy and thermal decomposition techniques. Coordination of ligands to the silver ions was confirmed by IR spectroscopy. IR data clearly indicate that NSAID anions are bonded in a monodentate mode. The thermal behavior of complexes was studied by TG, DTG and DTA methods in air. Upon heating all compounds decomposed progressively to silver oxide, which was the final product of pyrolysis.